Aid Motivation in Early and Mature Partnerships: Is there a difference? - Anders Olofsgård; Maria Perrotta Berlin; Emmanuel Frot (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2012)
We argue that the nature of aid flows early on in a bilateral partnership may be different from that at a later stage. Commercial and strategic interests may carry particular weight after a significant regime change when new relationships need to be established, whereas development concerns come to carry greater weight as the relationship matures. We test this argument using the natural experiment of the break-up of communism in Central and Eastern Europe and the former Soviet Union. By looking at the allocation of aid across recipients, how that allocation has changed over time, and the urgency by which donors entered certain markets, we get a sense of the donors' changing priorities. We find that trade flows and geographical proximity lead to more aid during the early period, 1990-95, but not after that. On the other hand, political openness and natural disasters have no effect in the early going but are correlated with more aid in the later time period. We also find that donors are in more urgency to enter into countries with higher per capita incomes and with which they trade, but they also prioritize more democratic countries in this respect. Our results hold up to a thorough sensitivity analysis, including using a gravity model to instrument for bilateral trade flows. Our findings may have implications for what to expect about partnerships, and the role of aid, emerging between Western donors and new regimes put in place by the Arab Spring.
Keywords: C26; F35; P30; 330; Foreign aid; aid allocation; transition countries